Background Radiation Survey at Major Dumpsites in Freetown, Sierra Leone (Journal of Nuclear Technology in Applied Science, 2021)
Dumpsites in Freetown the capital city of Sierra Leone have become major areas for urban agriculture. Moreover, many youths in communities around dumpsites scavenge various materials including scrap metals and sachet plastics from the dumpsites on a daily basis for survival. The two notable dumpsites, Kingtom and Granville Brooke dumpsites are open dumpsites that accommodate all types of mixed solid wastes some of which may emit or have the potential to emit radiation. In-situ measurement of the radiation dose rate was conducted on the two sites using a portable Radiagem survey meter and a Geographical Positioning System (GPS). Ten (10) measurements were made for each dumpsite. The result of the radiation measurements showed that the mean equivalent dose rate for the Kingtom and Granville Brooke dumpsites are 0.8 mSvy^(-1) and 1.1 mSvy^(-1) respectively. These values revealed that the Kingtom dumpsite has slightly higher value than the permissible limits of United Nations Scientific Committee on the Effect of Atomic Radiation (UNSCEAR) and lower than the permissible limits of International Commission on Radiological Protection (ICRP); whereas for the Granville Brooke dumpsite the mean equivalent dose rate is higher than both the permissible limits set by UNSCEAR and ICRP. It is therefore justifiable to conclude that both dumpsites, Kingtom and Granville Brooke could be unsafe in the near future from the cumulative effect of radiation exposure for workers, scavengers and other individuals exposed to loads of wastes in the dumpsites
Keywords: Dose rate; Dumpsites; Exposure; Radiation; Scavenger